Tricholepis elongata DC. (Asteraceae), a new record for Nepal - Pandey , A. K.; Chaudhary , L. B. (Rheedea, 1994)
The genus Tricholepis is, so far, reported to have only one species, viz., T. furcata DC. in Nepal. In this paper, we are reporting a second species of the genus, T. elongate DC., in this Himalayan Kingdom.